Euthanasia and the principle of human dignity (International Seven Journal of Multidisciplinary, 2024)
The general objective of this article is to address the institute of euthanasia, focusing on the right to life and the principle of human dignity. The specific objectives are: to interpret the right to life as a good protected by the Federal Constitution of 1988; to present doctrinal definitions and differences between euthanasia, dysthanasia and orthothanasia; to address the concrete cases of euthanasia that have occurred throughout history. The methodology used to develop the research was the deductive-bibliographic method. The conclusion is that euthanasia is a way of extending living with dignity, since the principle of the dignity of the human person seeks to accompany man from his conception to his last breath of life; and the practice of euthanasia promotes death with dignity for those who can no longer bear an embarrassing and agonizing situation that hurts their dignity.